2022
DOI: 10.3390/su142013111
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs’ Responses to COVID-19 Crisis: A Holistic Dynamic Capabilities Perspective in the Saudi Food and Beverage Sector

Abstract: The COVID-19 pandemic has been an active crisis for businesses around the globe. This paper adopts the Dynamic Capabilities (DC) theory to investigate factors that may account for differences in entrepreneurial marketing (EM) adoption and entrepreneurial marketing opportunities during two stages of the recent COVID-19 pandemic, namely the full and partial closure. The existing study provides useful insights into the functioning of entrepreneurial marketing that make the related opportunities and challenges vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 90 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…Referring to the fruit and vegetable supply chain in Meknes (Morocco), Saidi et al [137] observed that the crisis prompted the emergence of new and more sustainable food supply methods, such as mutualized and local sourcing, as well as reduced food waste, leading the move towards sustainability. [165]; AlTarrah et al [121]; Belton et al [208]; Ben Hassen et al [145]; Ben Hassen et al [6]; Ben Hassen et al [141]; Dimassi et al [127]; Elgammal et al [171]; Ghali-Zinoubi [183]; Hamade [130]; Kaitibie et al [146]; Saidi et al [137]; Saidi et al [138]; Sobaih and Moustafa [179]; Sundarakani and Onyia [193]; Taybeh et al [119]; Zainal et al [124] 25 (16.55%) Consumption (including food services and food waste)…”
Section: Agriculture Subsectors and Food Chain Stagesmentioning
confidence: 99%
See 3 more Smart Citations
“…Referring to the fruit and vegetable supply chain in Meknes (Morocco), Saidi et al [137] observed that the crisis prompted the emergence of new and more sustainable food supply methods, such as mutualized and local sourcing, as well as reduced food waste, leading the move towards sustainability. [165]; AlTarrah et al [121]; Belton et al [208]; Ben Hassen et al [145]; Ben Hassen et al [6]; Ben Hassen et al [141]; Dimassi et al [127]; Elgammal et al [171]; Ghali-Zinoubi [183]; Hamade [130]; Kaitibie et al [146]; Saidi et al [137]; Saidi et al [138]; Sobaih and Moustafa [179]; Sundarakani and Onyia [193]; Taybeh et al [119]; Zainal et al [124] 25 (16.55%) Consumption (including food services and food waste)…”
Section: Agriculture Subsectors and Food Chain Stagesmentioning
confidence: 99%
“…Bouzidi and Abdellaoui [79]; Dimassi et al [127]; El Bilali et al [135]; Elgammal et al [171]; El-Haddad and Zaki [102]; Faour-Klingbeil et al [206];…”
Section: Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all of the sustainable products that iHerb sells are cosmetics only" (Interview 7, S/F, 19Y). According to Elgammal et al [67], several young Saudi entrepreneurs started their businesses during the COVID-19 pandemic and adopted sustainable and green practices for their business model in the restaurant industry, but perhaps they failed to spread the word among Gen Z through their marketing strategies.…”
Section: Tpb: Perceived Behavioral Control Influence On Sustainable P...mentioning
confidence: 99%